Modeling of distribution of pressure in a heterogeneous oil-bearing reservoir - Lubkov, М. V.; Mosiichuk, К. О. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2021)
For the non-stationary problem of piezoconductivity, a numerical model of pressure distribution in an oil reservoir is proposed, which is based on a combination of well-known finite difference and finite element methods. The output data take into account the heterogeneity of the distribution of filtration characteristics across the reservoir. The pressure distributions obtained in this way correlate well with already-known ideas about reservoir operation at a late stage of development. A version of the calculation scheme with injection wells is considered. The results of calculations are visualized in the form of three-dimensional diagrams of reservoir pressure distribution. Recommendations are given for choosing a rational field development technology at a late stage of exploitation in order to increase the oil recovery rate in a heterogeneous reservoir.